Identifying microRNAs associated with anxiety proneness in a cohort of South African adolescents - Jansen van Rensburg, Danielle (Stellenbosch : Stellenbosch University, 2023)
Jansen van Rensburg, Danielle. 2024. Identifying microRNAs associated with anxiety proneness in a cohort of South African adolescents. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/e75a9276-9a36-473b-a6b5-6d2fca1357c6